Evaluating Security Mechanisms for Wireless Sensor Networks in IoT and IIoT - Zhukabayeva, Tamara; Buja, Atdhe; Pacolli, Melinda (Universitas Muhammadiyah Yogyakarta, 2024)
In the era of interconnected digital ecosystems, the security of Wireless Sensor Networks (WSN) emerges as a pivotal concern, especially within the domains of the Internet of Things (IoT) and the Industrial Internet of Things (IIoT). However, the very nature of WSNs—being distributed, resource-constrained, and often deployed in unattended environments—poses unique cybersecurity challenges. A main issue and challenge remains their Cybersecurity in communication. In this paper, we provide a systematic review focused on three themes including 1) techniques for secure communication in WSN; 2) algorithms and methods for intrusion detection in WSN; and 3) IoT and IIoT security concerning WSN. It has provided the results of its own for the publications made in the data analysis of three themes. The paper also has a simulation experiment to investigate the behavior of WSNs under sinkhole attacks—one of the prevalent threats to network integrity. Utilizing the Contiki OS Cooja simulator, the experiment carefully evaluates the performance of existing detection algorithms and introduces a novel method for identifying and neutralizing malicious nodes. Our simulation discloses unconventional communication patterns during sinkhole attacks running RPL protocol, emphasizing the effectiveness of our detection mechanisms against cyber threats. Particularly, the introduction of a malicious node (Node 13) significantly disrupted network communication, with traditional security mechanisms failing to immediately detect and isolate the threat. The scope of future research work will include the broader spectrum of cyber threats beyond sinkhole attacks, exploring advanced detection mechanisms, and machine learning-based security protocols for enhanced trust and transparency in WSN communications.